Growth response of tomatoes to application of bacterial-coated NPK fertilizer in a pot experiment - Hindersah, Reginawanti; Kaffah, Ruhnayati; Aisyah, Ayu Siti; Setiawati, Mieke Rochimi; Arifin, Mahfud (Kultivasi, 2024)
Nitrogen-fixer and phosphate-solubilizer bacteria increase the chemical-fertilizer efficiency and soil health. Bacterial-coated NPK fertilizer is a novel approach for intensifying biofertilizer application in vegetable production. The study aimed to observe the compatibility between two Azotobacter species and two Bacillus species, their population on two formulations of bacterial-coated NPK fertilizer (BCN), and the effect of BCN dose on growth, N and P content, and their uptake in tomato shoots. The compatibility test was performed using the streak method. The population of Azotobacter and Bacillus were counted for two formulations of NPK fertilizer coated by solid biofertilizer (5% and 10%) and zeolite (1% and 5%). The pot experiment was conducted in a randomized block design with four treatments and six replications. The treatments were 100% recommended doses of conventional NPK fertilizer (700 kg/ha) and 100%, 80%, and 60% doses of BCN. The results showed four bacterial species were compatible, indicated by synergistic growth on the plate agar. The BCN formula using 5% liquid inoculant and 5% zeolite has higher cell viability. The BCN enhanced stem thickness and leaves number but did not change the plant height, dry weight, N and P content, and their uptake in shoots. Applying 60% of BCN caused greater stem thickness and leaf number. Despite being insignificantly different from another treatment, that dose increased the biomass and the shoot uptake of N and P. The NPK fertilizer coated by Azotobacter and Bacillus has the potency to increase tomato growth and NPK fertilizer dose.